A sociological examination of the gift economy : envisioning the future - Katunarić, Vjeran (Emerald Publishing Limited, 2023)
With the advent of colonialism and the monetarized market economy, the gift economy, once a widely embedded cultural and economic practice, has become a niche of modern diplomacy, often serving as the means for corruption rather than human connection. In presenting an overview of the history and development of the gift economy, Vjeran Katunaric defines this exchange as a form of communication, similar to language, rather than an exchange that is merely material. By examining different theoretical approaches, including neoclassical, radical feminist, and conservative Christian views, the chapters explore how nonlinear forms of development may contribute to correcting the failures of competitive markets. Katunaric advocates for the gift economy as a means for introducing balance between planning and the market, as well as between the public and private sectors of the economy. In this way, a sense of restoring, and restorative, peace may be spread around the globe, along with a more equitable distribution of financial resources. On the whole, A Sociological Examination of the Gift Economy presents gift-giving as an intuitive path toward a viable economy, society, and culture here on Earth, and even toward an amiable engagement with our cosmic surroundings in the future.